The performance of steel fibre reinforced concrete with waste glass as partial replacement of fine aggregate - Yusuf, A M; Ali, N (2023)
This paper discusses the performance of steel fibre reinforced concrete with part of substitution of sand with waste glass in concrete mix. Glass consists mainly of silica, which is a natural raw substance like sand. Glass is completely recyclable, and it can be recycled indefinitely without losing any of its quality or purity. Waste glass powder was utilized as a partial replacement of fine aggregate with 0%, 10%, 20 and 30% by the volume in C30 grade of concrete and addition of 0.5 % steel fibre by volume fractions of hooked end steel fibre and 0.5 water cement ratio. All samples were evaluated following 28 days curing period. The aim of this study is to investigate the workability of concrete, to determine the compressive and tensile strength of concrete and to identify the optimum percentage of steel fibre reinforced and waste glass. From the experimental results, it was found that the study achieved a maximum compressive strength of 32.9 N/mm² at 30% replacement of fine aggregate with waste glass, slightly surpassing normal concrete. Additionally, the highest tensile strength of 3.9 N/mm² was achieved at 20% replacement, surpassing normal concrete. The optimum percentages determined were 20% for fine glass replacement and 0.5% for steel fiber addition. It can be concluded that scenario of waste glass concrete approach could be perceived as a sustainable and environmentally friendly product in the near future